1997
DOI: 10.1128/mcb.17.5.2658
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the (Recombinant) Endogenous Immunoglobulin Heavy-Chain Locus Requires the Intronic Matrix Attachment Regions

Abstract: The elements which regulate gene expression have traditionally been identified by their effects on reporter genes which have been transfected into cell lines or animals. It is generally assumed that these elements have a comparable role in expression of the corresponding endogenous locus. Nevertheless, several studies of immunoglobulin heavy-chain (IgH) gene expression have reported that the requirements for expressing IgH-derived transgenes differ from the requirements for expression of the endogenous IgH loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 44 publications
7
33
0
Order By: Relevance
“…1 A) (ref. 20 and M.J.S., unpublished observation). Loss of E or of both E and the MARs resulted in cells in which expression was variegated, such that two types of stable subclones could be isolated: those that continued to make WT levels of the heavy chain and those that had lost the ability to express the heavy chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A) (ref. 20 and M.J.S., unpublished observation). Loss of E or of both E and the MARs resulted in cells in which expression was variegated, such that two types of stable subclones could be isolated: those that continued to make WT levels of the heavy chain and those that had lost the ability to express the heavy chain.…”
Section: Discussionmentioning
confidence: 99%
“…The MARs recombinant, in which the MARs are the only intronic regulatory elements in the J-C intron, was used to generate the MARs-ϩ and MARs-Ϫ subclones, which are active and silent for IgH expression, respectively (18,19). ⌬, a recombinant with a complete deletion of the intronic elements, was used to generate the subclones ⌬-ϩ and ⌬-Ϫ , in which IgH is active or silent, respectively (14,20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is worthwhile to consider the putative functions of MARs at the IgH and Ig loci. By reporter gene assays in cell lines or transgenic mice, MARs flanking the enhancer E were shown to modulate IgH gene chromatin accessibility (31) and transcription in both positive and negative manners (27)(28)(29)(30). Similarly, MAR associated with the Ig intronic enhancer is thought to be involved in Ig gene transcription, demethylation, recombination, and somatic hypermutation (18,(33)(34)(35)(36).…”
Section: Figmentioning
confidence: 99%
“…In the immunoglobulin heavy chain (IgH) locus, MARs flank the intronic enhancer E and are in close proximity to V H promoters (22)(23)(24)(25)(26). Reporter gene assays in cell lines and transgenic mice have suggested that these MARs exert both positive and negative effects on IgH gene transcription and promote long range chromatin accessibility (27)(28)(29)(30)(31). A highly conserved MAR is also found 200 base pairs (bp) upstream of the intronic immunoglobulin (Ig) enhancer in mouse, human, and rabbit (22,32).…”
Section: Cd8mentioning
confidence: 99%